Antioxidant, photoprotective and inhibitory activity of tyrosinase in extracts of Dalbergia ecastaphyllum - Morais, Daniel Vieira de (2018)
Dalbergia ecastaphyllum is a native Brazil plant with importance for beekeeping, and widely used in folk medicine. For the first time, the extracts of this plant were assessed for the presence of hydrophilic and lipophilic antioxidants, as well as inhibition of tyrosinase, free radicals scavenging and sunscreen protection. The antioxidant activity was evaluated by free radical scavenging (DPPH) and β-carotene bleaching assay. The tyrosinase inhibitory activity was evaluated and calculated the EC50. The photoprotective activity was measured using different concentrations of D. ecastaphyllum extracts. The Sun Protection Factor (SPF) of the samples was higher than 6, and the sample from Ilhéus showed the most pronounced photoprotective effect. Sample from Canavieiras presented the highest antioxidant activity by free radical scavenging DPPH and β-carotene bleaching method, with 92.41% and 48.34%, respectively. All samples inhibited the tyrosinase, especially the sample from Prado that was most effective (124.62 μg.mL-1). Significant negative correlation was found between flavonoid contents and inhibition of tyrosinase. The overall results provide relevant information about the Dalbergia ecastaphyllum species, indicating as potential material to cosmetic and pharmaceutical industry.